Mechanisms of Tumor Necrosis Factor-Alpha Inhibitor-Induced Systemic Lupus Erythematosus - Yen, Chung-Yang; Yu, Sheng-Jie; Chen, Yi-Ming; Lai, Kuo-Lung; Wu, Yi-Da; Liao, En-Chih; Hsieh, Ching-Liang (Frontiers in Medicine, 2022)
Systemic lupus erythematosus induced by biologics mainly results from tumor necrosis factor-alpha remains unclear. The objectives of the study were to investigate the mechanisms of tumor necrosis factor-alpha inhibitor-induced systemic lupus erythematosus. Peripheral blood mononuclear cells obtained from thirteen psoriasis patients were cultured and treated with the following: untreated control, Streptococcus pyogenes with or without different biologics. The supernatants were collected for cytokines assay. Analysis of cytokine expression revealed that IL-2 and IL-10 levels decreased only in the TNF-α inhibitor-treated groups but not in the groups treated with biologics involving IL-17, IL-12/IL-23 or IL-23 inhibitor mechanisms (p<0.001, p<0.05). The IFN-γ/IL-13 ratio increased significantly in patients with SLE inducing biologics to S. pyogenes induction only compared with non-SLE inducing biologics to S. pyogenes induction only (p=0.001). IL-2 and IL-10 depletion and a shift to the Th-1 pathway in the innate response are the correlated mechanism for tumor necrosis factor-alpha inhibitor-induced systemic lupus erythematosus.